Speaking Self-Efficacy of EFL Students of Pre-Service Teaching Program in EFL Classroom Setting - Darmawan; Alam, Satria P.; Nirma, Oliva Nurhayati (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2021)
The standing grown of academic self-efficacy as a theoretical framework of independent contributor to task performance of language skills such as speaking has been widely recognized. Considerable amount of researches has also found self-efficacy in EFL context is still roughly challenging. The present research attempts to explain speaking self-efficacy of 35 EFL students of pre-service teaching program who enrolled in speaking advanced class in EFL classroom setting. The result showed the average percentage of student’s self-efficacy in the mastery of speaking skill was 79% which was high. The highest point of those questionnaires was students believed on their personal ability in the mastery of speaking skill (82%). while the lowest point of questionnaires was factors’ influencing students’ in public speaking in EFL classroom setting (77%). The average percentage of students’ self-efficacy in the mastery of speaking skill can grow with effort was categorized as high scale (79%). This research also revealed that students’ sources of self-efficacy based on their positive experiences of task accomplishments, observing role model performances, verbal persuasions, their effort, persistence/resilience that they exerted when obstacles arise, and emotional states. Self-efficacy level of one student with another’s was different despite having the same score and it has nothing to do with gender. Individuals with high levels of self-efficacy approach difficult tasks as challenges to master rather than as threats to be avoided